Agro-Economic Productivity of Rice- Rabi Croprice Systems in Northwestern Drought-Prone Areas of Bangladesh (SAARC Journal of Agriculture, 2022)
Productivity and economics of different rabi crop-based systems were evaluated at farmers’ field in Durgapur upazilla of Rajshahi district, Bangladesh to select the best rabi crop(s) for fitting in the T. Aman rice - rabi crop – DDS Aus rice pattern. Nine rabi crops namely, (1) Mustard, (2) Potato, (3) Lentil, (4) Field pea, (5) Radish, (6) Cabbage, (7) French bean, (8) Carrot and (9) Tomato were cultivated during the rabi season in between the two rice crops to form nine cropping patterns. The experiment used Randomized Complete Block Design (RCBD) with three replications. Aman rice variety BRRI dhan57 was transplanted on 12 July 2017 and harvested on 28 October 2017, while, Aus rice variety BRRI dhan28 was sown in the dry cultivated land on 16 March 2018 and harvested on 24 June 2018 while rabi crops were sown/transplanted on 28 November 2017. Proper agronomic management practices were adopted for all the crops in the patterns. Data on yield and related attributes of DDS Aus rice were recorded at harvest. In addition, the yield of Aman rice and all the rabi crops were recorded. In addition, rice equivalent yield of each rabi crop, system yield (total yield of all the crops in the sequence), cost of production, gross return and benefit cost ratios (BCR) of all the patterns were recorded. Results revealed that yield of dry direct seeded Aus rice cv. BRRI dhan28 did not differ significantly due to different rabi crops grown under the respective patterns. The system yield was the highest in T. Aman rice –tomato – DDS Aus rice pattern (19.62 t ha-1) and the lowest with T. Aman rice -mustard – Aus rice pattern (14.63 t ha-1). Since the market price of a rabi crop changes from year to year, the net profit of a pattern depends on the yield of a crop grown in rabi season. Therefore, any of the nine rabi crops under the trial can be successfully cultivated in between the two rice crops under Aman rice – rabi crop –Aus rice patterns. However, the present study concludes that any of the nine rabi crops can be grown in between the two rice crops but carrot, French bean, mustard, field pea, and tomato could be the most profitable ones for the T. Aman rice – rabi crops –DDS Aus rice patterns.SAARC J. Agric., 19(2): 85-94 (2021)